Coronary computed tomography and triple rule out CT in patients with acute chest pain and an intermediate cardiac risk profile part 1: s dimpact on patient management - Grüttner, Joachim; Fink, Christian; Walter, Thomas; Meyer, Mathias; Apfaltrer, Paul; Saur, Joachim; Süselbeck, Tim; Traunwieser, Dominik; Kralev, Stefan Borissov; Borggrefe, Martin; Schönberg, Stefan; Henzler, Thomas (European journal of radiology, 2013)
Objective: To evaluate the impact of coronary CT angiography (coronary CTA) or “triple-rule-out” CT angiography (TRO-CTA) on patient management in the work-up of patients with acute chest pain and an intermediate cardiac risk profile. Materials and methods: 100 patients with acute chest pain and an intermediate cardiac risk for acute coronary syndrome (ACS) underwent coronary CTA or TRO-CTA for the evaluation of chest pain. Patients with a high and low cardiac risk profile were not included in this study. All patients with significant coronary stenosis >50% on coronary CTA underwent invasive coronary catheterization (ICC). Important other pathological findings were recorded. All patients had a 90-day follow-up period for major adverse cardiac events (MACE). Results: Based on a negative coronary CTA 60 of 100 patients were discharged on the same day. None of the discharged patients showed MACE during the 90-day follow-up. Coronary CTA revealed a coronary stenosis >50% in 19 of 100 patients. ICC confirmed significant coronary stenosis in 17/19 patients. Among the 17 true positive patients, 9 underwent percutaneous coronary intervention with stent implantation, 7 were received intensified medical therapy, and 1 patient underwent coronary artery bypass surgery. A TRO-CTA protocol was performed in 36/100 patients due to elevated d-dimer levels. Pulmonary embolism was present in 5 patients, pleural effusion of unknown etiology in 3 patients, severe right ventricular dysfunction with pericardial effusion in 1 patient, and an incidental bronchial carcinoma was diagnosed in 1 patient. Conclusion: Coronary CTA and TRO-CTA allow a rapid and safe discharge in the majority of patients presenting with acute chest pain and an intermediate risk for ACS while at the same time identifies those with significant coronary artery stenosis.
Available online 29 June 2012
Gesehen am 25.06.2018